The Effect of Three Scion Varieties and Grafting Techniques on the Success of Durian (Durio zibethinus) Seedling Grafting - Maryamah, Maryamah; Ismadi, Ismadi; Rafli, Muhammad; Hafifah, Hafifah; Khaidir, Khaidir (Yayasan Pertanian Tropika Indonesia (YPTI), 2021)
Durian (Durio zibethinus) is a Southeast Asian plant with a high nutritional content, delicious taste, and many good benefits. Durian has a high economic value with a wide and varied market range (traditional to modern markets). This shows that durian is a commodity with a lot of potential for development. The increase in production is inseparable from various problems in the cultivation aspect, especially in the provision of quality durian seeds. Durian plants are generally propagated vegetatively. Vegetative propagation of durian can be done by grafting. In durian grafting, various varieties are used as scion. These varieties have been known to have their respective advantages and markets. This research aims to determine the effect of three varieties of scion and grafting techniques on the success of durian grafting. The research used a factorial randomized block design (RBD) consisting of two factors, which are the scion varieties and grafting techniques. There are three varieties of scions, which are umpang duk (V1), monthong (V2) and bintan (V3). Meanwhile, the grafting technique consists of top grafting (T1) and side grafting (T2).